A Study on the Procedure of Polymerization and Its Characterization: - (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The term supra-molecular chemistry, which was coined by Jean-Marie Lehn, means “Chemistry beyond the molecule”. While individual molecules consist of atoms joined by covalent bond, supra-molecular chemistry makes use of intermolecular interaction like hydrogen bonds, π-stacking and electrostatic forces bringing molecules together to form larger species. Hydrogen bonding enables compounds containing electronegative functional groups to interact with protons to form extended arrays. Molecules with aromatic rings can stack together by virtue of π-π interactions.